Role of TLR4 rs4986790A>G and rs4986791C>T Polymorphisms in the Risk of Inflammatory Bowel Disease - Ran Ao; Ying Wang; Dao-Rong Zhnag; Ya-Qi Du (Gastroenterology Research and Practice, 2015)
Objective. The present meta-analysis investigated the contribution of TLR4 rs4986790A>G and rs4986791C>T genetic polymorphisms in increasing the risk of inflammatory bowel disease (IBD). Methods. Databases were searched using a combination of keywords related to TLR4 and IBD. Relevant studies were selected based on strict inclusion and exclusion criteria. Meta-analysis of the data extracted from the selected studies was performed using CMA 2.0 statistical analysis software. Results. Out of the 70 studies retrieved by database search, only 13 studies were eligible for inclusion in this meta-analysis and these 13 studies contained a total number of 4409 IBD patients and 5693 healthy controls. The meta-analysis results demonstrated that TLR4 rs4986790A>G polymorphism is associated with an increased risk of IBD (allele model: OR = 1.268, 95% CI = 1.124~1.431, and P<0.001; dominant model: OR = 1.240, 95% CI = 1.090~1.409, and P=0.001). Similarly, TLR4 rs4986791C>T polymorphism also conferred an increased risk of IBD (allele model: OR = 1.259, 95% CI = 1.092~1.453, and P=0.002; dominant model: OR = 1.246, 95% CI = 1.072~1.447, and P=0.004). Conclusion. Our meta-analysis results demonstrate that TLR4 rs4986790A>G and rs4986791C>T genetic polymorphisms are associated with the etiopathogenesis of IBD.